An Empirical Study of Internet-Based ICT Adoption Among SMEs in Southern Malaysia - Tan, Khong Sin (2009)
Small and Medium Enterprises (SMEs) are a key economic sector in Malaysia. Malaysian government has actively promoted the development and growth initiatives such as ICT implementation to advance SMEs’ overall economic agenda over the past decades. Realising the prominence of SMEs as a main contributor to the country’s GDP and employment as well as the ICT as an enabler to leapfrog Malaysia to achieve Vision 2020, this thesis, therefore, examines the factors and adoption patterns of Internet-based Information and Communication Technologies (ICTs) among SMEs in Malaysia. Diffusion of Innovation Theory (DIT), and Unified Theory of Acceptance and Use of Technology (UTAUT) underpin the conceptual framework in this empirical research study. This research study used questionnaire-based survey to collect data from 406 managers/owners of SMEs in the southern region of Malaysia, Melaka and Johor.